Features of the morphostructure and of the local calcium distribution in dried blood drops of the patients with brain tumors - Maslova, Galina T.; Buloichik, Janne I.; Zajogin, Anatoli P.; Mavrichev, Anatoli S.; Derzhavets, Liliya A.; Trubetskaya, Antonina S.; Titova, Anastasija V. (Journal of the Belarusian State University. Physics, 2019)
The morphology of dried blood plasma drops of the patients with brain tumors of different grades and the local spatial distribution of calcium by volume in the facies analyzed has been studied. The structural peculiarities of dried blood drops from the patients with brain tumors of different grades and with metastatic brain tumors have been revealed. The possibility to use the features of the dried drop structural formation and of the local spatial calcium distribution as an additional source of information for diagnosis making and elucidation has been estimated. The proposed methods enable one to control the course of treatment and to check up the dynamics of the developing pathology.
Keywords: biological fluid; drop morphology; laser atomic-emission spectrometry; double laser pulses; spatial distribution; layer-by-layer analysis; calcium